Effect of nanoscale particles incorporation on microhardness of polymers for oral prosthesis - Goiato, Marcelo Coelho (Contemp Clin Dent, 2016)
OBJECTIVES: This study aimed to evaluate the influence of the incorporation of pigments on surface hardness of four acrylic resins subjected to thermocycling and analyze their elemental composition using energy dispersive X-ray spectroscopy (EDS). MATERIALS AND METHODS: Twenty-one discs of each resin were fabricated, whereas seven had no additive, seven had 3% of nanoscale pigments and last seven had 10% of them. The percentage was obtained by measuring the total weight of each resin disc. Besides, seven discs composed by only nanoscale pigments were also fabricated, totalizing 91 discs. The pigment was weighed by using an analytical balance (BEL Analytical Equipment, SP, Brazil). The surface hardness was measured through a hardness tester machine before and after thermocycling (5–55°C, for 2000 cycles). Data were analyzed by ANOVA and Tukey's test (P < 0.05). The chemical composition of the discs composed only by nanoscale pigments was analyzed with EDS test. RESULTS: Hardness of all resins decreased after thermocycling. The lowest values were observed on the discs with 3% of nanoscale pigments and discs fabricated only with them. EDS showed the presence of titanium dioxide. CONCLUSION: Discs with 7% of pigments (after thermocycling) showed higher hardness values.